The effect of corporate governance and audit practices on reducing earnings management in the UK - Shen, Jia (2020)
The study investigates earnings management of the UK listed companies and the role of corporate governance and audit in reducing earnings management. While top managers are supposed to act in the best interest of the shareholders and other stakeholders of the company, they have their own interests and as insiders they have more information about the company. This is known as the principal-agent problem that leads to agency costs, involving manipulation of the company financial statements, also known as ‘books cooking’ or ‘earnings management’. There were quite a number of corporate scandals leading to loss of shareholder value, as well as to other significant losses to the company stakeholders in the aftermath of earnings management. This study contributes towards decreasing the problem of earnings management by exploring how corporate governance and audit quality could contribute towards lower earnings management. For the purpose of the analysis, data on FTSE350 companies is used, including their historic financial statements information and also their board of directors’ data. Earnings management is proxied by discretionary accruals, which are changes in accruals that are not related to the extent of company operations. Regression analysis is then used to evaluate the effect of corporate governance and audit quality on earnings management.